EVALUASI EFEKTIVITAS KEBIJAKAN PENDIDIKAN DALAM MENINGKATKAN KUALITAS GURU: LITERATUR REVIEW - Mulyadi, Mulyadi; Agustin, ⁠Weli; Nurhalimah, Dilla; Latina, Nevi; Azizah, Shafiqah Ali (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The quality of education is a primary factor in creating a nation's competitiveness, with teachers playing a vital role in the learning process. However, efforts to improve teacher quality in Indonesia face complex challenges, including issues of welfare, pedagogical competence, and suboptimal systemic support. This study aims to evaluate the effectiveness of implemented educational policies in improving teacher quality based on a literature review. The method used is library research with a qualitative approach through thematic analysis of various relevant literature studies. The results indicate that policies such as teacher certification and continuous training have a positive impact on teachers' economic welfare but are not always followed by a significant improvement in pedagogical performance. Furthermore, the Merdeka Curriculum policy provides flexibility in teaching but faces implementation challenges, especially related to teacher readiness and inadequate supporting infrastructure. The conclusion of this study is that although educational policies have the potential to improve teacher quality, their effectiveness depends on comprehensive implementation and continuous support, as well as the need for further research to explore factors influencing the success of these policies.